Effects of AMD3100 subconjunctival injection on alkali burn induced corneal neovascularization in mice - Peng, Liang-Hong (International Journal of Ophthalmology Press, 2011)
AIM: To investigate the therapeutic effects of local and systemic administration of AMD3100 for alkali burn induced corneal neovascularization (CNV) in mice. METHODS: CNV was induced in vivo by alkaline burn of cornea in C57BL/6 mice. AMD3100 was administrated topically by subconjunctival injection or systemically by intraperitoneal injection for 7 days; balanced salt solution was administrated topically or systemically as a control respectively. Inflammatory index was evaluated by slit-lamp biomicroscopy and inflammatory cells infiltrated to cornea tissue were detected by histologic analysis at multiple time points. CNV was compared between the local and systemic treated mice 2 weeks after alkali burn, as quantified by CD34 immunostaining. Fluorescence-Activated Cell Sorter Analysis was used to investigate the mobilizing effects of EPC in mice after subconjunctival injected or intraperitoneal injected AMD3100. Immunohistochemistry was used to detect the expression of endothelial progenitor cells (EPC) marker proteins VEGFR2 and CD34. RESULTS: Three days after alkali burn, infiltration of inflammatory cells was found in corneal tissue. At the first 7 days of local injection group, the number of inflammatory cells was significantly lower than that in systemic injection group. CNV could be seen at the 7(th) day, and at the 14(th) day reached the peak, then started to decrease. The number of CNV in the subconjunctival injection group was 7.57±1.26 per 0.034mm(2), compared to a number of 14.87±2.21 per 0.034mm(2) in the control group (P<0.05). On the contrary, the number of CNV in the intraperitoneal injection group was a little higher than that in the control group, 16.34±1.53 per 0.034mm(2) vs 13.26±1.87 per 0.034mm(2). The research also showed that intraperitoneally, but not subconjunctivally injected AMD3100 could mobilize EPC. On the other hand, subconjunctival, but not intraperitoneally injected AMD3100 could reduce the expression of EPC marker proteins. CONCLUSION: In mice locally administrated AMD3100 can reduce the number of alkali burn induced CNV. The number of inflammatory cells and inflammatory responses in corneal tissue.